Limnic Condition In Rheotrhopic Peat Type As the Origin of Petai Coal, Central Sumatra Basin, Indonesia - Prayitno, Budi (UIR PRESS, 2016)
Petrographic coal is the study of organic and inorganic components of bearing coal formation. This study aims to determine the composition, depositional facies, type and stage of the genesis of coal in the area of research. This research method using a diagram approach Diessel, 1986, Calder et al., 1991 to determine the depositional facies and peat ecosystems formation of coal carrier. Microscopic observations using Carl Zeiss Microscope and Point Counter Model F was conducted to determine the micro-organic components of coal. Based on microscopic investigation of the overall sample average abundance maceral vitrinite reached 66.3%, 30.32% mineral matter, maceral liptinite 3:26%, and to absent maceral inertinit no indicates oxidation process that occurs during the decomposition of organic matter. Syngenetic depositional pyrite component type spread sporadically on the surface of the coal seam in the form frambiodal and particulates. Facies deposition of coal based on the calculation of tissue prevetion index versus gelification index show faises limnic while the calculation of ground water index versus vegetation index show atmosphere rheotropic mires (correlation +) supported the absence maceral inertinit and funginite, hypothesized water level in stable condition was high watertable during the decomposition process takes place in an atmosphere ph 6-8 and eh balanced. Average rate comparison gelifikasi the preserved tissues of plant cells (tellocolinite) is smaller than the 23.6% plant cell tissue is not preserved (desmocollinite) amounted to 52.6% indicated from plants of the type herbaceous plant.